MBE growth and morphology control of ZnO nanobelts with polar axis perpendicular to growth direction - Kennedy,OW; Coke,ML; White,ER; Shaffer,MSP; Warburton,PA (Materials Letters, 2018)
In quasi-one-dimensional polar nanostructures the relative orientation of the long and polar axes will determine how the polarity of the nanostructure may be exploited for applications. Here we present the growth by molecular-beam epitaxy of quasi-1d ZnO nanostructures (specifically nanobelts) with the polar axis perpendicular to the growth axis. We demonstrate the control of nanostructure morphology by growth temperature. Our work represents a key milestone towards the development of future polarization-engineered oxide heterostructures embedded in quasi-1d nanodevices.